Corporate social responsibility: Is it a pillar in relationships with customers? - Filipe, S. (2015)
Although academic research around Corporate Social Responsibility has registered an improvement, there is still a need for empirical studies expanding the knowledge of customers’ perceptions about Corporate Social Responsibility and its impact on the relationships with companies. Therefore, this paper aims to examine the impact of costumers’ perceptions about Corporate Social Responsibility of their grocery retail in long-term relationships. In order to address the object of the present study, a convenience sample of Portuguese customers answered an online questionnaire and the collected responses were analysed using Structural Equations Modelling. The main results show that customers’ perceptions of Corporate Social Responsibility is determinant for successful relationships between grocery retail and their customers mainly through more positive satisfaction and trust. Implications of the results and future research are also discussed.